Opioid maintenance, weaning and detoxification techniques: where we have been, where we are now and what the future holds. (July 2013) - Plunkett, Anthony; Kuehn, Devon; Lenart, Mark; Wilkinson, Indy
SUMMARY  Medically supervised opioid withdrawal is a complex and constantly evolving exercise in multimodal therapy that draws from the expertise of a variety of clinical specialties. Acute substitution and weaning has been performed utilizing opioid agonists, partial agonists (e.g., buprenorphine), mixed agonist/antagonists (e.g., Suboxone®), and α2 adrenergic agonists. While thousands of patients are being treated with these 'classic' opioid-withdrawal techniques, traditional treatment approaches are being challenged by the emergence of innovative techniques based on an understanding of the neurochemistry of addiction. Pharmacotherapy with controlled withdrawal is currently the most reliable method of opioid detoxification, but, as translational medicine continues to advance and genomic markers for opioid sensitivity and dependence are identified, the future shows great potential for growth and change.